On mediation historical, legal, anthropological and international perspectives - Härter, Karl, 1956-; Hillemanns, Carolin; Schlee, Günther (Integration and conflict studies ;, 2020)
"Exploring mediation and related practices of conflict regulation, this book takes an interdisciplinary approach that includes historical, legal, anthropological and international perspectives. Divided into three sections, the volume observes historical and current relations between mediation and the criminal justice system and provides anthropological perspectives and case studies to explore mediation and arbitration in international arenas. In this regard, the book provides an innovative perspective on mediation and new insights into conflict regulation"--